2002
DOI: 10.1046/j.1467-789x.2002.00074.x
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in Malaysia

Abstract: This study was undertaken to assess the recent data on Malaysian adult body weights and associations of ethnic differences in overweight and obesity with comorbid risk factors, and to examine measures of energy intake, energy expenditure, basal metabolic rate (BMR) and physical activity changes in urban and rural populations of normal weight. Three studies were included (1) a summary of a national health morbidity survey conducted in 1996 on nearly 29 000 adults > or =20 years of age; (2) a study comparing ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
82
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(100 citation statements)
references
References 8 publications
15
82
2
1
Order By: Relevance
“…The prevalence of health problems like obesity and type II diabetes is normally associated with the lack of physical activity [19] [20]. Therefore, there is an urgent need to incorporate exercise as a vital element in any health promotion campaign.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of health problems like obesity and type II diabetes is normally associated with the lack of physical activity [19] [20]. Therefore, there is an urgent need to incorporate exercise as a vital element in any health promotion campaign.…”
Section: Resultsmentioning
confidence: 99%
“…Findings of previous studies indicate that regular physical activity helps strengthen the heart muscles and also minimises heart diseases, a leading cause of deaths in Malaysia [17] [18]. In addition, it can help to reduce the escalating number of obese Malaysians [19]. According to published statistics, Malaysia was ranked sixth in the Asia-Pacific region for obesity and topped the list in South-East Asia for both obesity and diabetes [20] [21].…”
Section: Discussionmentioning
confidence: 99%
“…Sustained economic growth and rapid urbanization may have resulted in a decreased level of PA among Malaysians. Moreover there is increasing concern about the growing burden of NCDs in Malaysia (5,6). A national survey about metabolic syndrome has reported that prevalence was 30.1% according to the IDF (International Diabetes Federation) definition (7).…”
Section: Introductionmentioning
confidence: 99%
“…Historically, obesity was considered to be primarily a problem of western societies [1,2,3,4,5] but, recently, obesity has also emerged as an important health concern in eastern societies [6,7,8,9]. Obesity has increased with the change in lifestyle and eating habits in Korea.…”
Section: Introductionmentioning
confidence: 99%